The difference in passive tension applied to the muscles composing the hamstrings – Comparison among muscles using ultrasound shear wave elastography. (August 2016) - Nakamura, Masatoshi; Hasegawa, Satoshi; Umegaki, Hiroki; Nishishita, Satoru; Kobayashi, Takuya; Fujita, Kosuke; Tanaka, Hiroki; Ibuki, Satoko; Ichihashi, Noriaki
Abstract: Background: Hamstring muscle strain is one of the most common injuries in sports. Therefore, to investigate the factors influencing hamstring strain, the differences in passive tension applied to the hamstring muscles at the same knee and hip positions as during terminal swing phase would be useful information. In addition, passive tension applied to the hamstrings could change with anterior or posterior tilt of the pelvis. Purpose: The aims of this study were to investigate the difference in passive tension applied to the individual muscles composing the hamstrings during passive elongation, and to investigate the effect of pelvic position on passive tension. Methods: Fifteen healthy men volunteered for this study. The subject lay supine with the angle of the trunk axis to the femur of their dominant leg at 70° and the knee angle of the dominant leg fixed at 30° flexion. In three pelvic positions ("Non-Tilt", "Anterior-Tilt" and "Posterior-Tilt"), the shear elastic modulus of each muscle composing the hamstrings (semitendinosus, semimembranosus, and biceps femoris) was measured using an ultrasound shear wave elastography. Results: The shear elastic modulus of semimembranosus was significantly higher than the others. Shear elastic modulus of the hamstrings in Anterior-Tilt was significantly higher than in Posterior-Tilt. Conclusion: Passive tension applied to semimembranosus is higher than the other muscles when the hamstring muscle is passively elongated, and passive tension applied to the hamstrings increases with anterior tilt of the pelvis. Highlights: The passive tension applied to hamstrings during passive elongation was examined. The passive tension applied to semimembranosus is the highest in hamstring muscle. The passive tension applied to hamstring increases with anterior tilt of pelvis.